Development of Intersection Management Strategy Due to Opening of Sumatra Toll Road - S. Rahma; R. A. E. Putra (Journal of Science and Applicative Technology, 2019)
The main role of a transportation network is providing optimum services for transportation network. Over the time, the population is increasing and the needs of reliable transportation network also increased. Transportation network consists of node and connector. According to the condition, the provision of reliable transportation network facilities should be able to optimize the node and the link. In the real condition, there’s a gap between the existing transportation network conditions with the optimum transportation network conditions, as a result the existing transportation network is not able to serve the transportation movement that occurred. Based on this information, research entitled Development of Intersection Management Strategy Due to Opening of Sumatra Toll Road. The objective of this study are: a) Generating traffic flow through the Simpang Polsek Sukarame, Bandar Lampung. b) Evaluating the traffic composition through Simpang Polsek Sukarame, Bandar Lampung. c) Evaluating services intersection parameters needed in evaluating the intersection. d) Determining the intersection strategy of intersection due to the opening of the Sumatra Toll Road. The study is conducted by using Macroscopic Modeling approach using PTV Vissum application and microscopic evaluation using MKJI 1997. In the research, there are several types of data needed. These data are classified into primary and secondary data. Primary data required include: a) Traffic Counting Data, TC Data implemented at Simpang Polsek Sukarame. Traffic Counting data is used as a database for the validation of the transportation model. b) Road geometry data is taken at all connector of Simpang Polsek Sukarame. The Geometry consist of the road width and shoulder width. Geometry data is used for capacity calculation, delay, and saturation degree. From the results of transport modelling that will be evaluated the service level of the intersection based on the parameters of degree of saturation, delay, and speed of vehicles through the intersection. The Result of the model shows that The queue length increasing from 10.66 m to 16.64 m or increasing for around 60% and the average delay increasing from 7 s to 13.43 s or increasing around 95%. It will be concluded that the addition of toll road traffic is affecting the intersection performance.